2005
DOI: 10.1007/s10327-005-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of A2 and D strains of Soybean mosaic virus, which caused a recent virus outbreak in soybean cultivar Sachiyutaka in Chugoku and Shikoku regions of Japan

Abstract: Coat protein sequences of two isolates in strain A 2 and five isolates in strain D of Soybean mosaic virus (SMV), which caused a recent mosaic outbreak in soybeans (cv. Sachiyutaka) in Chugoku and Shikoku in Japan, were compared to published data on 15 other Asian-origin isolates. Sequence comparison and cluster analysis showed that SMV isolates of strain A 2 from these districts were closely related, as were those of strain D, but strains A 2 and D were not. Thus, the two strains may have different origins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…In Japan and China, alternative strain classification systems have been reported. The Japanese system classifies SMV isolates into strains A, B, C, D and E, and considers both biological and sequence data (Saruta et al, 2005). The Chinese system uses several soybean differential lines to classify SMV strains SC1-21 (Li K. et al, 2010;Ma et al, 2016;Wang et al, 2003).…”
Section: Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan and China, alternative strain classification systems have been reported. The Japanese system classifies SMV isolates into strains A, B, C, D and E, and considers both biological and sequence data (Saruta et al, 2005). The Chinese system uses several soybean differential lines to classify SMV strains SC1-21 (Li K. et al, 2010;Ma et al, 2016;Wang et al, 2003).…”
Section: Variabilitymentioning
confidence: 99%
“…Since then, a rapidly increasing number of complete genome sequences of isolates from China, Iran, Japan, South Korea and North America have been determined, enabling studies of virus evolution in relation to inoculum source and deployed resistance genes (Ahangaran et al, 2013;Chen Y.-X. et al, 2017;Chowda-Reddy et al, 2011a;Domier et al, 2011;Hajimorad et al, 2003;Saruta et al, 2005;Seo et al, 2009a;Zhou et al, 2015). Analyses have shown that SMV cistrons are subject to different selection pressures (Seo et al, 2009b;Zhou et al, 2015).…”
Section: Variabilitymentioning
confidence: 99%
“…All these soybean genotypes resistant to SMV are the valuable resource for breeding programs. Since the seed-borne, aphid-transmitted SMV is genetically variable and continually evolving via RNA recombination and spontaneous mutations by its own errorprone RdRp, strong directional selection would lead to the occurrence of resistance-breaking isolates (Choi et al, 2005;Saruta et al, 2005;Gagarinova et al, 2008a). Incorporation of multiple resistance genes into a soybean genotype (cultivar or variety) through gene pyramiding becomes a priority for soybean breeders to develop durable resistance to SMV.…”
Section: Breeding Using Natural Resistance Genesmentioning
confidence: 99%
“…It is worth to mention that SMV grouping based on their sequence similarity may be a more reliable approach. As more and more SMV isolates are sequenced, the complete genome sequences and partial gene sequences can be used to study the phylogenetic relationship and molecular variability (Frenkel et al, 1989;Saruta et al, 2005;Schirmer et al, 2005;Wetzel et al, 2006;Gagarinova et al, 2008b;Seo et al, 2009). The outcomes of these studies will certainly provide new insights into the evolutionary process of SMV in relation to its natural hosts.…”
mentioning
confidence: 99%
“…This disease is caused by soybean mosaic virus (SMV). The spread of this disease has resulted in serious crop losses in some regions of the world (Choi et al 2005, Saruta et al 2005, Gagarinova et al 2008, Khatabi et al 2012, Banerjee et al 2014. In China, SMV was grouped into 22 strains (SC1-22) (Li et al 2010.…”
mentioning
confidence: 99%